1988
DOI: 10.1093/oxfordjournals.jbchem.a122343
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Activation and Kinetic Properties of Three Distinct Forms of Protein Kinase C from Rat Brain1

Abstract: Three types of protein kinase C, designated types I, II, and III, were purified from rat brain cytosol, and have been shown to correspond to the cDNA clones gamma, beta, and alpha, respectively. Their relative activities in the whole brain tissue were roughly 26, 49, and 25% with H1 histone as a substrate. Type II enzyme was an unequal mixture of two subspecies (roughly 1:7) encoded by beta I and beta II sequences which differ from each other only in a short range of their carboxyl-terminal end regions. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
2

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(100 citation statements)
references
References 0 publications
13
85
2
Order By: Relevance
“…The rat brain PKC that was found to be capable of activating PLD consisted of a mixture of the 01, p and y isofoirns [ 161. In order to determine which isoforms were active, they were resolved by hydroxylapatite chromatography [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rat brain PKC that was found to be capable of activating PLD consisted of a mixture of the 01, p and y isofoirns [ 161. In order to determine which isoforms were active, they were resolved by hydroxylapatite chromatography [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PKCa, /I and y were purified from rat brain as described previously [21]. After resolution by hydroxylapatite chromatography, the identity of the isoforms was confirmed by immunoblot analysis using specific antisera.…”
Section: Purification Of Protein Kinase C Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…> Na'). Because Ba2'-can activate some Ca?+-dependent processes (Knight et al, 1988;Sekiguchi et al, 1988;Przywara et al, 1993), the enhanced ethanol inhibition of Ca2+/Ba'+ flux may be due to activation of a secondary Ca"-dependent mechanism. Injection of EGTA could reduce the ethanol inhibition of Ca'+ responses if this involved an intracellular Ca2+-dependent mechanism; however, EGTA is a slow Ca'+ chelator and was only present in micromolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The activation process involves the formation of a quaternary complex between kinase C, calcium, phospholipid and phorbol ester. In some studies, it has been shown that calcium is not absolutely necessary for the action of PMA, whilst the effect of phorbol esters is dependent upon the presence of phospholipids [7,19]. However, in the course of our study, as a control, we tested the effect of PMA on the kinase activity of the fractions eluting from the DE 52 column in the absence of both calcium and phosphatidylserine.…”
Section: Effect Of Phorbol Estersmentioning
confidence: 98%